Estimating Employment Effects of Powerlinks Transmission Limited Project in India and Bhutan - International Finance Corporation (International Finance Corporation, Washington, D.C., 2017)
In 2003 International Finance Corporation (IFC) committed a loan of US $75 million to Powerlinks Transmission Limited (PTL) a joint venture company, to construct power transmission lines that helped evacuate hydropower from Bhutan to a number of States in north and east India. Unlike most studies which tend to focus on jobs created through construction and O&M (category one jobs) of power projects, this study looks at employment effects more comprehensively and also estimates category two jobs that are created- i.e. those jobs that are created as the increase in power supply brought by PTL helps firms expand their output and hence create more jobs. We also specifically focused on the impact of increased reliability in power supply through reduced power outages, on job creation. The purpose of the transmission system is to expand the capacity of the Indian grid, connecting the power surplus regions of east and northeast India with the power deficit region of north India. PTL commenced construction in November 2003 and achieved commercial operation in 2006. This is the first private sector transmission project in India as well as in a developing country in Asia. The objective of this study is to assess the employment effects of the Power links project in both India and Bhutan. Wherever possible, an effort was made to assess over development impact on welfare of people in India and Bhutan.